Natural Volatile Compounds as Antifungal Agents Against Monilinia fructicola In Vitro and in Composite Edible Coatings for Sustainable Disease Reduction and Fruit Quality Preservation During Prolonged Cold Storage of Fresh Japanese Plums - Alvarez, María Victoria; Palou, Lluís; Taberner, Verónica; Pérez-Gago, María B. (MDPI, 2025)
The antifungal activity of natural extracts, essential oils (EOs), and pure volatiles against Monilinia fructicola, the main causal agent of brown rot of stone fruits, was evaluated in in vitro tests. Cinnamon (CI), lemongrass (LE), geraniol (GE), and myrrh (MY) Eos were the most effective antifungal agents and, hence, selected as ingredients of composite edible coatings (CECs) formulated with hydroxypropyl methylcellulose (HPMC) and lipidic components. In in vivo curative experiments with ‘Black Gold’ plums artificially inoculated with M. fructicola and incubated for up to 10 days at 20 ◦C, brown rot incidence was reduced by up to 49% with CECs containing 4 g/kg LE, 2 g/kg GE, or 5 g/kg MY. These CECs were then evaluated for brown rot control and quality maintenance of ‘Angeleno’ plums stored for up to 6 weeks at 1 ◦C and 90% RH, followed by a shelf-life period of 4 days at 20 ◦C. After 3 weeks, CECs containing GE and MY reduced brown rot incidence by 45 and 70%, respectively. After 6 weeks plus shelf life, all CECs reduced brown rot severity (lesion size) by 30–50%. Regarding fruit quality, coated plums showed higher firmness than uncoated control plums, and the CEC containing GE significantly reduced weight loss after 6 weeks plus shelf life. Moreover, physicochemical quality attributes (titratable acidity, soluble solids content, and volatile compounds) and sensory properties (overall flavor, off-flavor, firmness, and external appearance) of coated plums were not negatively affected by CEC application. Furthermore, all coated plums exhibited more gloss than uncoated fruit. Overall, the CEC-GE formulation was the most effective in reducing decay and maintaining the postharvest quality of cold-stored plums, showing the best potential as a sustainable alternative for plum postharvest preservation.